Marketing digital en redes sociales y su contribución a la identidad de marca en alojamientos turísticos familiares. - Ramos Cavero, María Jeanett (2022)
ABSTRACT Objective: To analyze the contribution of digital content in the brand identity of family lodgings in the Lima Region, Peru, in 2021. This aims their efforts to digital marketing able to strengthen the brand-consumer relationship through social networks that have created a revolution in the way we interact with the world today. Method: It is descriptive, with nonprobabilistic sampling, it was selected 10 family tourist lodgings with the best ratings on the travel platforms Booking and TripAdvisor belonging to the Lima Region. Results: High participation in social media: Facebook, Instagram, and YouTube, applying digital tools such as images, news, and videos as attractive audiovisual content for consumers. Conclusions: Digital content contributes to the approach to the consumer, providing a more agile, attractive, and bidirectional communication to reinforce brand identity in family lodgings.